Amplion, Inc. (July 2016) - Taylor, Seth; Carroll, Adam; Lord, Jessi
Amplion, Inc. (OR, USA) is focused on progressing the primary drivers of precision medicine. Focused on enabling the front end of the healthcare value chain, pharmaceutical developers and diagnostic test developers, Amplion zeros in on the research and market components that will make precision medicine a reality. With BiomarkerBase™, Amplion's flagship product, Amplion provides evidence-based biomarker information that support the key strategic decisions pharmaceutical and diagnostic developers need to make to be successful in the emerging world of precision medicine. A passion for saving lives and improving patient outcomes using precision medicine inspires Amplion's product BiomarkerBase™. A unique combination of hard science and data science positions Amplion to surface the relationships of biomarkers and clinical evidence that gives pharmaceutical and diagnostic companies unique insight into the technical realities and market opportunities provided by biomarkers.